2018
DOI: 10.3390/nu10111766
|View full text |Cite
|
Sign up to set email alerts
|

Changing to a Low-Polyphenol Diet Alters Vascular Biomarkers in Healthy Men after Only Two Weeks

Abstract: Bioactive dietary compounds play a critical role in health maintenance. The relation between bioactive compound intake and cardiovascular health-related biomarkers has been demonstrated in several studies, although mainly with participants who have altered biochemical parameters (high blood pressure, high cholesterol, metabolic syndrome, etc.). The aim of this study was to evaluate if adopting a diet low in polyphenol-rich food for two weeks would affect vascular biomarkers in healthy men. In a crossover study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…We focused the report on 27 articles as shown in the PRIMA diagram [ 25 - 51 ]; 13 of these studies were carried out in Spain [ 26 - 28 , 33 , 35 , 38 , 41 , 44 - 46, 48, 49, 51 ], 3 studies were carried out in the USA [ 25 , 31 , 47 ], 3 studies were carried out in Italy [ 30 , 36 , 40 ], 4 studies were carried out in other European Union countries [ 32 , 34 , 39 , 50 ] and 4 studies were carried out in Australia [ 29 , 37 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We focused the report on 27 articles as shown in the PRIMA diagram [ 25 - 51 ]; 13 of these studies were carried out in Spain [ 26 - 28 , 33 , 35 , 38 , 41 , 44 - 46, 48, 49, 51 ], 3 studies were carried out in the USA [ 25 , 31 , 47 ], 3 studies were carried out in Italy [ 30 , 36 , 40 ], 4 studies were carried out in other European Union countries [ 32 , 34 , 39 , 50 ] and 4 studies were carried out in Australia [ 29 , 37 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The data were mainly derived from RCT studies with or without a parallel-group design. 2 studies had a crossover RCT design [ 28 , 29 ]. In most of the cases, there was an intervention group following MD and a control group with its usual diet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolic impact is rapid, as shown in a crossover study in which a reduction in foods containing polyphenols was already reflected in a change in biomarkers, such as the ratio of thromboxane A 2 and prostaglandin I 2 , in the urine at the first control at 2 weeks [ 39 ].…”
Section: Components In Olive Oil With a Health Impactmentioning
confidence: 99%
“…Therefore, we consider that the most important and effective strategy against these atherosclerosis-related acute aortic syndromes is to establish preventive measures that can be effective before the onset of diseases. Several epidemiological studies have shown that a healthy flavonoid-rich diet could help prevent cardiovascular diseases [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%